Praktik Jual Beli Sistem Agensi pada Agen Herba Penawar Alwahida Indonesia di Kota Balikpapan dalam Perspektif Ekonomi Syariah - Basri, Pajrin; Darmawati, Darmawati; Taher, M (Universitas Islam Lamongan, 2024)
Sharia economics is an economic system that occurs after economic principles become its working guidelines, influenced or limited by Islamic teachings. There are problems with the large number of agents and consumers, such as not practicing buying and selling using an agency system according to the provisions set by HPAI. The agency sells HPAI products to agents and consumers at the same price. This is because there are some agents who shop at agencies, but sometimes the agency forgets to enter the agent's membership number, which has an impact on prices that should be discounted but become normal prices. The method in this research is using qualitative research with the Field Research type and using a case study approach. The data collection technique is observation, interviews and documentation, the data analysis technique used is first condensing the data, then presenting the data and finally drawing conclusions from the data, as well as using techniques data validity. The results of the research are that the practice of buying and selling the agency system at the Herba Penawar Alwahida Indonesia agent in Balikpapan from a sharia economic perspective namely murabahah contract, where the agency tells the initial price when buying and selling, as well as the product it is sold using herbal ingredients and has transparency in its processing, so that sharia economic values ​​can truly be implemented in the buying and selling transaction process for Herba Penawar Alwahida Indonesia products.